Complicated pressure–temperature path recorded in the eucrite Padvarninkai. (26th July 2021) - Miyahara, Masaaki; Yamaguchi, Akira; Ohtani, Eiji; Tomioka, Naotaka; Kodama, Yu
Abstract: High‐pressure minerals in the eucrite Padvarninkai were investigated. Parts of anorthitic plagioclase and tridymite in the host rock of Padvarninkai vitrified, indicating that the shock pressure was 22–27 GPa. Tissintite, coesite, and a majorite‐bearing garnet occurred in the shock‐melt veins of Padvarninkai as high‐pressure minerals. Tissintite, kyanite, corundum, and dense plagioclase have occurred in the anorthitic plagioclase grains. The anorthitic plagioclase was melted and tissintite crystallized from the melt after the crystallization of kyanite and corundum. The residual melt became dense plagioclase by quenching. Tridymite has also melted and coesite crystallized from the melt. The formation of tissintite and coesite indicates that the shock pressure recorded in the veins was 2–13 GPa. The temperature increased drastically in the veins (>˜3000 K) compared with the host rock (<˜800 K). Parts of the tissintite and coesite became, respectively, amorphous (or anorthite) and quartz. Two different impact events may be recorded in Padvarninkai: The first impact event brecciated a part of the host rock, and the second impact event induced the melting of the brecciated portion, resulting in the formation of shock‐melt veins where the conditions are a high temperature and a relatively low pressure. In the veins, tissintite and coesite formed first, and parts of them underwent a back‐transformation due to a long cooling time.